Deskripsi Sikap Siswa Dalam Kesenangan Belajar Fisika dan Ketertarikan Memeperbanyak Waktu Belajar Fisika di SMAN Batanghari - Rini Siski Fitriani; Tari Okta Puspitasari; Defri Melisa (Jurnal Ilmu Fisika dan Pembelajarannya (JIFP), 2020)
The purpose of this study is to identify the attitude of pleasure in learning physics and interest in increasing the time to study physics. This type of research is quantitative research with descriptive method analysis. This study involved 151 students at SMAN 10 Batanghari. The instrument used was an attitude questionnaire with an indicator of pleasure in learning physics and an interest in increasing the time to study physics. The results of this study are the indicators of pleasure in learning physics, namely in the category of Fair with a percentage of 47% and the indicator of interest in increasing the amount of time studying physics in the category of Fair with a percentage of 62.3%. Based on these results the attitude of students towards learning physics at SMAN 10 Batanghari is good enough.